WHY ANIMAL DISSECTION IN THE SCHOOL? - Bagchi, Brotati (SCHOOL SCIENCE, 2013)
If there is one area of our interest where Newton’s third law of motion does not quite apply, it is most certainly to education. For every educational advance, there is an opposite but unequal and vehement reaction. This is almost a global phenomenon. In the US, for example, if one attempts to teach evolution, one is harassed by anti-evolutionists. Over a hundred years after Wilberforce and Huxley exhausted all their arguments, there are pockets of anti-evolution sentiment. While teaching the biology of sex, one is attacked by anti-sex educationists, despite climbing rates of AIDS. There are those who wish to prohibit schools from discussing matters that pertain to sex. One of the more recent trends is resentment of the use of organisms in the laboratory. In some states in the US there are laws that prohibit the use of animals in the classroom for any purpose whatsoever